Kajian Pemanfaatan Limbah Fly Ash Dan Bottom Ash Pada Konstruksi Lapisan Perkerasan Subbase Jalan - Florence Agustina Samosir; Alfian Malik; Yosi Alwinda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Fly ash and bottom ash (FABA) is one of the residues produced from the coal burning process which is included in hazardous and toxic waste. However, the content of FABA is one reason for the utilization of the waste has been used. The purpose of this study was to determine the utilization of fly ash and bottom ash in the subbase on the carrying capacity of the road and with the appropriate proportions to optimize profit utilization. This research is based on laboratory testing by testing the CBR of immersion by the 2018 Bina Marga standard. The subbase layer mixture was made in four variations. Variation I was without fly ash and bottom ash. In variations II and III fly ash and bottom ash were used as substitutes, and in variation IV fly ash and bottom ash were used as additives. Variation I with 0% fly ash and bottom ash content resulted in a CBR value of 64%. Variation II and variation III with 22% and 25% fly ash and bottom ash content resulted in CBR values of 93% and 84%. Variation IV with 25% fly ash and bottom ash content results in a CBR value of 73% so that all CBR values are fulfilled on the 2018 Bina Marga standard and fly ash and bottom ash are suitable for use in the mixture of road pavement layers. Keywords: Fly ash, Bottom ash, CBR, Subbase